Weight-bearing computed tomography in the identification of intercuneiform instability in Lisfranc lesion: a case report - Sousa Macedo, Rodrigo; Correa Paiva Fonseca, Fabio; Conde Bertelli, Vinicius Thiago; Barban Sposeto, Rafael; Diniz Fernandes, Túlio; Leme Godoy-Santos, Alexandre (Journal of the Foot & Ankle, 2026)
Lisfranc lesions have a high rate of diagnostic failure (> 30%), especially in isolated ligament injuries. Diagnostic delay is associated with chronic pain and instability of the middle foot. Weight-bearing computed tomography (WBCT) emerges as a promising tool. The objective of this report is to present a case in which this modality of examination identified intercuneiform instability not detected by conventional methods. Evaluation of a female patient, a marathon runner, with a Lisfranc injury after falling down stairs. Performed: weight-bearing radiography, comparative bilateral conventional tomography and weight-bearing computed tomography. Surgical exploration with evaluation under intraoperative radioscopy. Conventional examinations identified C1-M1, C1-M2, C2-M2 instability and plantar avulsion at the base of the second metatarsal. Weight-bearing computed tomography additionally showed intercuneiform asymmetry (C1-C2, which was not detected in the stress test under intraoperative radioscopy. Surgical exploration confirmed this instability, modifying the planning. Fixation performed with cannulated screws 3.5 mm and a dorsal plate. Weight-bearing tomography represents an advance in the diagnosis of Lisfranc lesions, especially hidden instabilities. When unavailable, systematic intraoperative exploration is indispensable for complete diagnosis and appropriate treatment.